The chromosomal abnormalities associated defects and outcomes of fetuses diagnosed prenatally with clubfoot (Annals of Medical Research, 2021)
Aim: To assess associated findings, chromosomal abnormalities and outcomes of the pregnancies diagnosed with fetal clubfoot.Materials and Methods: Ultrasonographic characteristics, pregnancy work-up and fetal outcomes of the pregnancies diagnosed with fetal clubfoot between January 2015 and October 2019 were evaluated retrospectively. Clubfoot was considered as complex or isolated depending on the presence or absence of additional structural abnormalities. The results of cases, which grouped according to the presence of additional abnormalities and laterality, were compared.Results: A total data of 46 pregnancies diagnosed with fetal clubfoot during the study period were included. The most associated abnormality with clubfoot was central nervous system (CNS) anomalies. Nineteen (41%) of fetuses were considered complex, and 27 (59%) were considered isolated. The ratio of the cases with poor outcomes was higher in the complex group than in the isolated group and was 15 (79%) and 1(3%) respectively (p=0.000 for bilateral group and p=0.013 for unilateral group). There were 7 (36%) cases with a chromosomal abnormality in the complex group and 1(4%) case in the isolated group. The deformity was unilateral in 16 (35%) and bilateral in 30 (65%) cases. The rate of poor outcomes was not different in cases with bilateral and unilateral clubfoot deformity (p=0.356).Conclusion: The prognosis of the fetuses diagnosed with clubfoot mostly depends on associated abnormalities. Therefore a careful evaluation of these fetuses must be performed even if karyotyping is normal. The laterality did not have any impact on the prognosis of cases with clubfoot.
Keywords: Clubfoot; congenital talipes eqinovarus; prenatal diagnosis; ultrasonography